Ekonomicnost' bega: opredelenie, ocenka, elementy i struktura, rezervy povyšenija - Kryazhev, V. D.; Tolstoy, E. V.; Marinina, N. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Running economy is a characteristic of energy consumption in human locomotion, estimated by metabolic costs of overcoming a unit of distance (minus the level of rest and air resistance). Measured in J/kg/m or mlO2/kg/km. For men and women, the economy is almost equivalent and has little sensitivity to running speed and approximately equals 4.19 J/kg/m. For elite runners, Europeans economy is estimated at 3.75-3.85 J/kg/m, for African runners this value is 3.35-3.45 J/kg/m. The structure of the elements that make up the economy of running has been developed. The main areas of improvement in economy indicators have been identified.